The Innovation Systems of Latin America and the Caribbean - Alberto Melo (Inter-American Development Bank, Research Department, 2001)
It is now widely recognized that we live in a knowledge-based economy; in fact, knowledge is the driving factor behind productivity growth. The share of knowledge-intensive sectors in the world economy`s value-added and employment has been rising for a number of years. This trend is particularly pronounced in the developed countries, where by 1999 knowledge-based industries share of GDP was already above 50 percent, up from 45 percent in 1985 (OECD, 1999; OECD, 2000a). Furthermore, knowledge-driven innovation has become a decisive factor in the competitiveness of both nations and firms.
Keywords: 330; Innovationspolitik; Forschungs- und Technologiepolitik; Lateinamerika; Karibische Staaten